Generosity, Access Frictions, and the Win–Win Region in Pharmaceutical Markets (*) - Kantarelis, Demetri (British Journal of Healthcare and Medical Research, 2026)
This paper develops a stylized theoretical framework in which a Pharmacy Benefit Manager (PBM) strategically chooses an access‑enabling strategy (AES) that reduces financial, administrative, and psychological barriers to prescription drug use. Higher AES lowers patient cost‑sharing, relaxes utilization frictions, and increases treatment uptake. Pharmaceutical firms set prices taking AES as given, while the PBM balances enrollee satisfaction, drug spending, and administrative costs; a regulator may further shape AES through actuarial value requirements, out‑of‑pocket maximum rules, or access‑based incentives. The model yields a central result: there exists a win–win region in which increasing AES simultaneously raises pharmaceutical profits, raises PBM profits, and improves welfare. This region emerges because access‑enabling investments expand demand, reduce transaction costs, and generate medical offsets that can outweigh higher drug spending. However, gains for patients, physicians, payers, and manufacturers do not necessarily extend to hospitals. By reducing avoidable complications and shifting care from high‑margin inpatient services to lower‑margin outpatient settings, higher AES can erode hospital profits. The framework provides a tractable way to analyze access as an endogenous strategic variable and clarifies when incentives for payers and manufacturers align—or conflict—with hospital financial viability.